Effects of anabaena lipoxygenase on whole wheat dough properties and bread quality. Issue 10 (28th August 2020) - Shi, Kexin; Wang, Pei; Zhang, Chong; Lu, Zhaoxin; Chen, Meirong; Lu, Fengxia
Abstract: The effects of the purified recombinant anabaena lipoxygenase (ana‐rLOX) on the rheological characteristics of whole wheat dough and the quality of bread were investigated. The lightness of whole wheat dough supplemented with ana‐rLOX was improved, which is superior to that of dough treated with benzoyl peroxide. The effect of ana‐rLOX on the strength of dough was analyzed by farinograph, extensograph, and dynamic rheological tests. Compared with the control, the stability time of dough treated with 40 IU/g ana‐rLOX increased by 35.4% and the farinograph quality number increased by 27.4%. In addition, the resistance to extension, as well as the elastic and viscous modulus, was improved by ana‐rLOX in a dose‐dependent manner. The height and specific volume of bread treated with ana‐rLOX increased by 17.3 and 15.2%, respectively, compared with the control, and the lightless, whiteness, and other textural parameters, such as hardness, springiness, chewiness, resilience, and gumminess, were significantly improved. Overall, the results of this study suggest the promising application of ana‐rLOX in enhancing quality of whole wheat flour. Abstract : The effects of purified recombinant anabaena lipoxygenase (ana‐rLOX) on the rheological properties of whole wheat dough and the quality of bread were investigated.